The Effect of Corporate Governance, Integrated Quality Management and Social Responsibility on Competitiveness and Operational Performance - J. Junaidi (Golden Ratio of Marketing and Applied Psychology of Business, 2022)
The purpose of this study is to analyze the effect of corporate governance, integrated quality management, and social responsibility on the competitiveness of manufacturing companies, analyze. The study was conducted on manufacturing companies with a population of 43 companies and determined a sample of 129 employees as respondents. The data from the questionnaire were analyzed using the SEM-AMOS. The study's results found social responsibility had insignificant effect on the competitiveness. This is because responsibility tends to be a moral spirit of the company which is not too related to the competitiveness that the company wants to achieve, so social responsibility in the form of environmental, social, economic, stakeholder, and voluntary dimensions has an insignificant impact on the company's competitiveness. Social responsibility has a positive and negative effect on the competitiveness. Besides that, social responsibility is related to the worker's social spirit and the social environment. Social responsibility has insignificant effect on the competitiveness. This is because the actualization of social responsibility is not directly related to competitiveness and improving corporate performance. Responsibility tends to be oriented towards aspects of worker psychology and working environment conditions, while competitiveness and operational performance are oriented towards achieving the results of the company's work.